Internal carotid artery hypoplasia in two cases - Akfirat, M; Cihangiroglu, M; Özdemir, H; Topsakal, C; Murat, A; Yildirim, H (W B Saunders Co Ltd, 2002)
[Abstract Not Available]
Keywords: Aneurysm; Agenesis; Absence